1992
DOI: 10.1037/0278-7393.18.3.509
|View full text |Cite
|
Sign up to set email alerts
|

Intact and long-lasting repetition priming in amnesia.

Abstract: In 2 experiments, we evaluated the ability of amnesic patients to exhibit long-lasting perceptual priming after a single exposure to pictures. Ss named pictures as quickly as possible on a single occasion, and later named the same pictures mixed with new pictures. In Experiment 1, amnesic patients exhibited fully intact priming effects lasting at least 7 days. In Experiment 2, the priming effect for both groups was shown to depend on both highly specific visual information and on less visual, more conceptual i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
167
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(194 citation statements)
references
References 63 publications
27
167
0
Order By: Relevance
“…Visual objects that are transformed by surface changes in left-right orientation or in size have been found to impair explicit, not implicit, performance (Biederman & Cooper, 1992;Cave & Squire, 1992;Cooper, Schacter, Ballesteros, & Moore, 1992;Schacter, Cooper, & Teadwell, 1993). A similar dissociation has been reported with the affect and recognition tasks.…”
Section: Discussionmentioning
confidence: 48%
“…Visual objects that are transformed by surface changes in left-right orientation or in size have been found to impair explicit, not implicit, performance (Biederman & Cooper, 1992;Cave & Squire, 1992;Cooper, Schacter, Ballesteros, & Moore, 1992;Schacter, Cooper, & Teadwell, 1993). A similar dissociation has been reported with the affect and recognition tasks.…”
Section: Discussionmentioning
confidence: 48%
“…The argument could be made that the observed reduction of latencies in Experiment 1, interpreted here as repetition priming, was critically mediated by explicit memory in some way. Although this possibility cannot be excluded, similar procedures to probe priming have been validated against performance in amnesic patients (Cave & Squire, 1992) and against measures of explicit memory (Mitchell & Brown, 1988), excluding the possibility of explicit mediation in these studies. A nonimplicit interpretation of the reduction of identification latencies for repeated odors in Experiment 1 can start with the fact that participants attempted to identify priming odors twice, whereas they attempted to identify control odors only once-and even relatively common odors are generally difficult to identify.…”
Section: Repetition Primingmentioning
confidence: 99%
“…Cave and Squire (1992), for example, asked amnesic patients and healthy participants to name pictures either once or twice at two retention intervals. Reduction in latency to name those shown previously against new pictures indicated repetition priming.…”
Section: Experiments 1 Repetition Primingmentioning
confidence: 99%
“…Past results have indicated that priming can occur at fairly high levels of visual object representation. Researchers have found, for example, that priming in object-naming tasks can persist across translations and reflections (Biederman & Cooper, 1991), changes in size (Biederman & Cooper, 1992), viewpoint (Bartram, 1974;Biederman & Gerhardstein, 1993), shading (Cave & Squire, 1992), texture, and color (Cave, Bost, & Cobb, 1996). Moreover, such effects have been found to persist over the course of minutes, days, and even weeks (e.g., Cave, 1997;Cave & Squire, 1992).…”
mentioning
confidence: 99%